Foveal Avascular Zone Area Quantification with OCT Angiography Following Successful Rhegmatogenous Retinal Detachment Repair - Portela, Mariana (2023)
INTRODUCTION: Visual prognosis after a rhegmatogenous retinal detachment (RRD) may relate to the vascular status of the macula. Recent works have demonstrated that optical coherence tomography angiography (OCTA) can reproducibly evaluate foveal avascular zone (FAZ) dimensions. The aim of this research was to study the FAZ area at the superficial and deep capillary plexus using OCTA after successful RRD repair and correlate this data with postoperative visual recovery. METHODS: This was a prospective case-control study that included all patients diagnosed between January and March of 2021 with an RRD that was successfully repaired with a single, uncomplicated surgical procedure (pars plana vitrectomy with gas tamponade). Two groups were created according to macula involvement (macula-on and macula-off) and control data was obtained from the fellow healthy eye. FAZ areas were independently measured by manually outlining the inner border of foveal capillaries of superficial (SCP) and deep capillary plexus (DCP) using OCTA system software. RESULTS: We included 12 eyes (6 macula-on and 6 macula-off) and 12 controls (12 patients). All eyes with RRD had significantly larger FAZ areas of both SCP (study group: 0.30 ± 0.09 mm2; control group: 0.26 ± 0.09 mm2; p<0.001) and DCP (study group: 0.37 ± 0.06 mm2; control group: 0.33 ± 0.05 mm2; p=0.002). In the macula-off group this difference was greater than in the macula-on group for both superficial (macula-off group=+0.051 mm2; macula-on group=+0.027 mm2; p=0.027) and deep (macula off group=+0.062 mm2, macula-on group=+0,023 mm2 , p=0.062) FAZ areas. Postoperative best corrected visual acuity was significantly higher in the macula-on group (macula-on group=0.81; macula-off group=0.55; p=0.029). CONCLUSION: FAZ area enlargement observed after a retinal detachment demonstrates that the latter may lead to an ischemic injury. When the macula is involved this damage may be greater which could explain a larger FAZ area. Slighter changes in FAZ area in macula-on RRDs may explain a better visual prognosis associated with this type of detachment.